Differential Effects of Angelicin Analogues on NF-κB Activity and IL-8 Gene Expression in Cystic Fibrosis IB3-1 Cells. (27th September 2017) - Lampronti, Ilaria; Manzione, Maria Giulia; Sacchetti, Gianni; Ferrari, Davide; Spisani, Susanna; Bezzerri, Valentino; Finotti, Alessia; Borgatti, Monica; Dechecchi, Maria Cristina; Miolo, Giorgia; Marzaro, Giovanni; Cabrini, Giulio; et al.
Abstract : The angelicin analogue 4, 6, 4′-trimethylangelicin (TMA) was recently reported as a strong inhibitor of nuclear factor- κ B (NF- κ B) activity and of the expression of the interleukin-8 (IL-8) gene in bronchial epithelial cells in which the inflammatory response has been challenged with P. aeruginosa, the most common bacterium found in the airways of patients affected by cystic fibrosis (CF). These findings encouraged us to analyze new synthetic analogues of TMA in order to evaluate their biological activities on human bronchial epithelial CF IB3-1 cells and to find more potent anti-NF- κ B agents exhibiting only minor antiproliferative effects. Analogues able to inhibit NF- κ B/DNA interaction at lower concentration than TMA were found and selected to investigate their biological activity on IB3-1 cells induced with TNF- α . In this biological system, NF- κ B-mediated IL-8 gene expression was investigated. Some analogues showed similar activity to the lead compound TMA. Other analogues displayed higher activities; in particular, the most interesting compounds showing relevant anti-inflammatory effects were found to cause 56–83% reduction of IL-8 mRNA expression at low concentrations (1–10 μ M), without changes in cell proliferation pattern, demonstrating their potential interest for a possible development of anti-inflammatory therapy of cystic fibrosis.